2012
DOI: 10.1016/j.lungcan.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic value of human copper transporter 1 (hCtr1) in patients with stage III non-small-cell lung cancer receiving first-line platinum-based doublet chemotherapy

Abstract: Background Recent studies have shown that human copper transporter 1 (hCtr1), the major copper influx transporter, is involved in the transport of platinum-based antitumor agents. We investigated the predictive and prognostic values of hCtr1, and cooper efflux transporters ATP7A and ATP7B, in patients with locally advanced non-small cell lung cancer (NSCLC) receiving first-line platinum-based chemotherapy. Methods From 2004 to 2009, we identified 54 consecutive stage III NSCLC patients who underwent first-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 31 publications
3
52
0
1
Order By: Relevance
“…The same correlation was seen with human CTR1 (hCTR1) in some tumor cells (Song et al, 2004;Zisowsky et al, 2007). Several subsequent studies confirmed this correlation and led to the suggestion that hCTR1, the major high-affinity copper transporter, also mediates platinum drug uptake (Pabla et al, 2009;Larson et al, 2009Larson et al, , 2010bChen et al, 2012;Kalayda et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…The same correlation was seen with human CTR1 (hCTR1) in some tumor cells (Song et al, 2004;Zisowsky et al, 2007). Several subsequent studies confirmed this correlation and led to the suggestion that hCTR1, the major high-affinity copper transporter, also mediates platinum drug uptake (Pabla et al, 2009;Larson et al, 2009Larson et al, , 2010bChen et al, 2012;Kalayda et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…A previous study has reported that hCtr1 expression is able to predict the prognosis of patients with advanced NSCLC that received platinum-based chemotherapy (16). Thus, in the present study, the expression of hCtr1, ATP7A and ATP7B proteins was detected in surgically resected NSCLC tissues to determine the association between the expression of these proteins with the histology, chemotherapy response, tumor stage, differentiation and prognosis in patients with resected NSCLC that received platinum-based treatment.…”
Section: Introductionmentioning
confidence: 86%
“…Ctr1 controls copper uptake, while ATP7A and ATP7B control the copper export from cells (23)(24)(25). Previous studies have identified that copper ion transport proteins are closely associated with the development of cisplatin resistance (16,26,27). These copper transporters include Ctr1 and ATP7B and ATP7A (23,28), which together regulate the overall intracellular cisplatin levels.…”
Section: A B Cmentioning
confidence: 99%
“…32 However, in clinical NSCLC specimens, only the copper uptake transporter CTR1, but not ATP7A or ATP7B, predicted clinical outcome after platinum-based chemotherapy. 33 In addition, the observation that NSCLC dose-response curves flatten at higher platinum dose-intensities 34 would be more in keeping with resistance being related to reduced uptake rather than increased efflux. 35 Validating functions of transport factors in NSCLC and incorporating them as biomarkers for platinum sensitivity into future clinical trials would be of significant clinical value.…”
Section: Platinum Concentration and Clinical Outcome In Nsclcmentioning
confidence: 99%